Effect of abnormal credit expansion and contraction on GDP per capita in ECOWAS countries. (29th August 2022) - Ozili, Peterson K.; Oladipo, Jide; Iorember, Paul Terhemba
Abstract: We investigate the impact of abnormal credit expansion and contraction on the gross domestic product (GDP) per capita (CGDP) of Economic Community of West African States (ECOWAS) countries. We analyse abnormal credit from two dimensions: first, the impact of abnormal credit contraction on CGDP and, second, the impact of abnormal credit expansion on CGDP. Using data for 10 ECOWAS countries from 1993 to 2021, we find evidence that abnormal credit contraction reduces the CGDP of ECOWAS countries. We also find some evidence that abnormal credit expansion reduces the CGDP of ECOWAS countries. More specifically, a unit increase in abnormal credit contraction decreases CGDP by 0.99%, whereas a unit increase in abnormal credit expansion decreases CGDP by only 0.1%. The findings confirm that 'too little' or 'too much' credit does not improve growth per person in immature financial systems. We also observe that banking sector solvency and a strong legal system have a positive effect on the CGDP of ECOWAS countries, while banking sector efficiency has a negative effect on CGDP.